2011
DOI: 10.1042/bj20110318
|View full text |Cite
|
Sign up to set email alerts
|

Retention in the Golgi apparatus and expression on the cell surface of Cfr/Esl-1/Glg-1/MG-160 are regulated by two distinct mechanisms

Abstract: Cfr (cysteine-rich fibroblast growth factor receptor) is an Fgf (fibroblast growth factor)-binding protein without a tyrosine kinase. We have shown previously that Cfr is involved in Fgf18 signalling via Fgf receptor 3c. However, as Cfr is also known as Glg (Golgi apparatus protein)-1 or MG-160 and occurs in the Golgi apparatus, it remains unknown how the distribution of Cfr is regulated. In the present study, we performed a mutagenic analysis of Cfr to show that two distinct regions contribute to its distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The golgi apparatus protein 1 (GLG1), also known as CFR, ESL-1 and MG-160, is a 135 kDa glycosylated single pass type I transmembrane protein that contains 16 cysteine-rich GLG1 repeats [41]. It is found in the golgi apparatus and on the cell surface membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The golgi apparatus protein 1 (GLG1), also known as CFR, ESL-1 and MG-160, is a 135 kDa glycosylated single pass type I transmembrane protein that contains 16 cysteine-rich GLG1 repeats [41]. It is found in the golgi apparatus and on the cell surface membrane.…”
Section: Discussionmentioning
confidence: 99%
“…GLG1 is able to bind with many different proteins making it an important regulatory protein and signal transducer. The localisation of GLG1 is a crucial determinant of GLG1 function and is influenced by two mechanisms: the transmembrane domain and cytoplasmic tail retain GLG1 in the golgi apparatus, whereas the cys-rich repeats destabilise the protein and GLG1 is recruited to the cell surface via processes of stability control [41]. It has also been reported that GLG1 can be released from the cell by proteolytic cleavage at the juxtamembrane region [42].…”
Section: Discussionmentioning
confidence: 99%